Photocatalytic Degradation of Heavy Metals Cd, Cu, Fe and Pb Using ZnO-Zeolite Nanocomposite - Ramadhini, Tri Karimah; Agustina, Tuty Emilia; Melwita, Elda; Wijayanti, Maria Siswi (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2023)
Heavy metals are the main pollutant substances in the environment. Heavy metals are a type of metal with high density and are very dangerous to living organisms, especially humans. Living organisms can adsorb the bioaccumulative and sedimentation of heavy metals that settle in water. Some compounds which found in wastewater including Cadmium (Cd), Copper (Cu), Iron (Fe), and Lead (Pb). These heavy metals cannot naturally degrade, additional processing is required before it being released into the environment. To prevent environmental pollution impacts, wastewater containing heavy metals must be handled properly and optimally. One method that can be applied for wastewater treatment is degradation by photocatalysis, utilizing the assistance of light. This research is to investigate the effect of pH and irradiation time on the degradation of Cd (cadmium), Cu (Copper), Fe (Iron), and Pb (Lead) heavy metals. To enhance the photocatalytic activity, the synthesis of ZnO-Zeolite nanocomposites was conducted. The ZnO-Zeolite nanocomposites produced were analyzed by SEM-EDX and XRD. The utilization of ZnO-Zeolite nanocomposites is deemed effective in reducing heavy metal concentrations. The degradation with Ultraviolet (UV) light exposure runs within 15-120 minutes with pH variation between 4-8. The degradation of heavy metal runs at 60 minutes and 120 minutes showing an optimum percentage removal of metals approaching 100%. The optimum pH values for Cd, Cu, Fe, and Pb are pH 8, pH 7, pH 6, and pH 8, respectively. The sequential metal degradation percentages are 98.96%, 95.43%, 96.07%, and 95.53%, respectively.